Синтез замещенных йодалкинов в присутствии ацетата кадмия (II) - Н. Г. Обосян (ՀՀ ԳԱԱ հրատ.)
A convenient and selective method for the preparation of substituted iodoalkynes based on the interaction of prop-2-yn-1-ol, prop-2-yn-1-yl acetate and 2-methylbut-3-yn-2-ol with iodine in the presence of readily available cadmium (II) acetate in ethanol has been developed by us. Առաջարկվել է տեղակալված յոդալկինների սինթեզի մատչելի եղանակ պրոպ-2-ին-1-ոլի, պրոպ-2-ին-1-իլ ացետատի ու 2-մեթիբուտ-3-ին-2-ոլի և յոդի փոխազդեցության հիման վրա` կադմիումի (II) ացետատի ներկայությամբ էթանոլում:
Keywords: Organic Chemistry